2018
DOI: 10.1016/j.wombi.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study showing women’s participation and empowerment in instrumental vaginal births

Abstract: This study shows how cooperation and empowerment of the woman are two key factors in order for the women to have a positive experience of their instrumental vaginal births. The study also shows that empowerment is created when the woman is actively engaged and participates in the birth process which gives her the feeling of being part of the team, creating an environment based on mutual understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Six studies were qualitative studies of maternity service users reporting the views and experiences of 73 women and 20 men from three high-income countries (Sweden, UK, USA) [23,26,[30][31][32][33]. The earliest study included in the qualitative evidence synthesis was from 2003 [23] and the most recent from 2015 [31].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies were qualitative studies of maternity service users reporting the views and experiences of 73 women and 20 men from three high-income countries (Sweden, UK, USA) [23,26,[30][31][32][33]. The earliest study included in the qualitative evidence synthesis was from 2003 [23] and the most recent from 2015 [31].…”
Section: Resultsmentioning
confidence: 99%
“…Four included survey studies [29,36,50,66] reported some free-text responses. These papers, along with the six included qualitative studies [23,26,[30][31][32][33] and the mixed-methods study [34] provided the starting point for our convergence coding matrix. In total 36 studies were included in the quantitative narrative synthesis, of which seven were from LMIC settings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations